2015
DOI: 10.1002/chir.22542
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Clobazam on High‐Performance Liquid Chromatography Chiral Stationary Phases

Abstract: Clobazam, a 1,5-benzodiazepin-2,4-dione, is a chiral molecule because its ground state conformation features a nonplanar seven-membered ring lacking reflection symmetry elements. The two conformational enantiomers of clobazam interconvert at room temperature by a simple ring-flipping process. Variable temperature HPLC on the Pirkle type (R)-N-(3,5-dinitronenzoyl)phenylglycine and (R,R)-Whelk-O1 chiral stationary phases (CSPs) allowed us to separate for the first time the conformational enantiomers of clobazam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Villani and co‐workers studied the dynamic behavior of 1,4‐benzodiazepin‐2‐ones , a well‐known class of pharmacologically active heterocyclic compounds with sedative, hypnotic, anxiolytic, and anticonvulsant properties (Table ). Medicinal chemistry investigations have shown that conformational chirality of the 1,4‐benzodiazepine core of these molecules plays a key role in determining their bioactivity .…”
Section: Dynamic Chromatography Of Atropisomeric Systems With Internamentioning
confidence: 99%
“…Villani and co‐workers studied the dynamic behavior of 1,4‐benzodiazepin‐2‐ones , a well‐known class of pharmacologically active heterocyclic compounds with sedative, hypnotic, anxiolytic, and anticonvulsant properties (Table ). Medicinal chemistry investigations have shown that conformational chirality of the 1,4‐benzodiazepine core of these molecules plays a key role in determining their bioactivity .…”
Section: Dynamic Chromatography Of Atropisomeric Systems With Internamentioning
confidence: 99%
“…Conformational changes are normally based on monomolecular mechanisms and, as such, do not require the assistance of a secondary molecular partner. Atropoisomerism is an intramolecular event that falls into this class of reactions, featuring pure first-order kinetics (Gasparrini et al, 1997a(Gasparrini et al, , 2000(Gasparrini et al, , 2001(Gasparrini et al, , 2002aDell'Erba et al, 2002;Andreani et al, 2004;Borsato et al, 2004;Dalla Cort et al, 2005;Lunazzi et al, 2010;Levi Mortera et al, 2012;Rizzo et al, 2013Rizzo et al, , 2014Rizzo et al, , 2015Chiarucci et al, 2014;Sabia et al, 2014Sabia et al, , 2016Menta et al, 2015). On the other hand, configurational isomerizations (i.e., processes involving rupture and reformation of chemical bonds) are commonly promoted by species that act as catalysts and that therefore do not modify their concentration during the interconversion (a bimolecular mechanism).…”
Section: Calculation Of Free Energy Activation Barriers and Their Entmentioning
confidence: 99%
“…In our work, the chiral resolution of prothioconazole and its chiral metabolite prothioconazole-desthio were performed on commercialized polysaccharide-based columns including Chiralcel OJ-H, Chiralpak IA, Chiralpak IB, Chiralpak IC, Chiralpak AY-H, Chiralpak AZ-H, 17 Lux Cellulose-1, 18 one kind of self-made Chiralcel OD, 17 and another pirkle type column (R,R)-Whelk-O1 19 (as shown in Figure 1B). The influences of mobile phase composition such as n-hexane/IPA or n-hexane/ethanol under normal phase conditions and ACN/water or methanol/water under reverse phase conditions were discussed.…”
Section: Introductionmentioning
confidence: 99%